DEVELOPMENT OF A COMMUNITY LITERACY PROGRAM TO INCREASE CHILDREN'S INTEREST IN READING IN RURAL AREAS - Eka Selvi Handayani; Euis Kusumarini; Moh. Imron Rosidi; Najamuddin Petta Solong; Dadang Muhammad Hasyim (Adiba Aisha Amira, 2023)
A vital part of life is reading. Reading has several advantages, including strengthening memory, expanding knowledge, and enhancing brain function. It is believed that developing literacy in children will lead them to better reasoning abilities, because the best learning can be obtained by reading. This research aims to describe a community literacy program to increase children's interest in reading in rural areas. The method used in writing this article is a literature review. The results obtained in this research are that the Community Literacy Program has an important role in improving literacy culture in children. Where children who usually feel bored studying alone at home can turn to a reading house to be able to study together while also being able to find entertainment with games.